2016
DOI: 10.1186/s12877-016-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

A Lebanese dietary pattern promotes better diet quality among older adults: findings from a national cross-sectional study

Abstract: BackgroundProper nutrition is critical for healthy aging and maintaining functional independence. Limited research has been done on the assessment of dietary patterns of older adults and their association with diet quality indices. This study was conducted to identify, characterize, and evaluate the dietary patterns and diet quality of older adults in Lebanon, a middle-income country undergoing nutrition transition.MethodsA cross-sectional population-based study was conducted on a nationally representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 61 publications
6
26
0
Order By: Relevance
“…In our study, the fieldworkers who conducted data collection had received extensive training to reduce judgemental verbal and non-verbal communication in order to minimize any social desirability bias. The FFQ and the IPAQ used in the present study were not validated in our population; however, these tools were previously used in dietary and physical assessment studies among Lebanese adults and the findings of these studies yielded plausible associations with obesity, MetS, diabetes and metabolic health ( 29 , 42 , 50 , 53 59 ) . Finally, the present study was confined to the urban setting of the Greater Beirut area; hence, findings pertinent to the consumption levels of foods may not be representative of less urban settings in the country.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the fieldworkers who conducted data collection had received extensive training to reduce judgemental verbal and non-verbal communication in order to minimize any social desirability bias. The FFQ and the IPAQ used in the present study were not validated in our population; however, these tools were previously used in dietary and physical assessment studies among Lebanese adults and the findings of these studies yielded plausible associations with obesity, MetS, diabetes and metabolic health ( 29 , 42 , 50 , 53 59 ) . Finally, the present study was confined to the urban setting of the Greater Beirut area; hence, findings pertinent to the consumption levels of foods may not be representative of less urban settings in the country.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, there are conflicting results in the studies evaluating the association between the SES and the dietary habits, which may be due to the disparities between developing and industrialized countries [36]. Studies conducted in Lebanon on older adults showed that subjects with higher income made healthier choices in their dietary pattern, thus having the purchasing power needed to access healthier food [37]. However, when evaluating the SES with childhood and adolescent's obesity and dietary habits, Nasreddine et al showed that in middle-income countries such as Lebanon, pediatric obesity appears to be predominant among high-income families [38].…”
Section: Discussionmentioning
confidence: 99%
“…Crowding index (CI), defined as the average number of people per room, excluding the kitchen and bathroom, was used as a proxy for socioeconomic status, whereby a lower CI was associated with a higher socio economic status [ 22 ]. Earlier investigations showed that CI was associated with adherence to certain dietary patterns in Lebanon [ 19 , 23 , 15 ].The lifestyle factors considered in this study were related to smoking and physical activity. Physical activity was assessed using the short Arabic version of the International Physical Activity Questionnaire [ 24 ].…”
Section: Methodsmentioning
confidence: 99%